Publisher Correction: Functional aspects of meningeal lymphatics in ageing and Alzheimer's disease. (6th December 2018) - Da Mesquita, Sandro; Louveau, Antoine; Vaccari, Andrea; Smirnov, Igor; Cornelison, R.; Kingsmore, Kathryn; Contarino, Christian; Onengut-Gumuscu, Suna; Farber, Emily; Raper, Daniel; Viar, Kenneth; Powell, Romie; et al.
Change history: In this Article, Extended Data Fig. 9 was appearing as Fig. 2 in the HTML, and in Fig. 2, the panel labels 'n' and 'o' overlapped the figure; these errors have been corrected online.